The Cambridge introduction to Walt Whitman - Killingsworth, M Jimmie (Cambridge University, 2013)
Focusing on his masterpiece 'Leaves of Grass', this volume offers a foundation for the study of Whitman. Alongside close readings of his major texts, there are chapters on Whitman's biography, the history & culture of his time, & the critical reception of his work.